Detection of ethanol in beverages using an electronic nose - Jaswir, Irwandi; A. M, Nurul Asyikeen; Akmeliawati, Rini (IIUM Press, 2011)
This study has bren successfully conducted to develop a method for rapid detection of ethanol (EtOH) content in beverages using IIUM-developed ~JMabk electronic nosc (E-Nose). E-Nose is a device that mimic human's olfactory system and is widely used in food analysis. However. E· Noses used in food industry are big and not portable, while the one used in this study is very handy and pra<;:tical for use. The differences betwc<;:n this project with other existing rcseart:hed is that It was used to dete<;:t EtOH <;:ontenl in beverages and the process paramelt:TS was optimized using Response Surface Methodology (RSM). The dala was analyzed using Design Expcn v6.0,8. Results from this study revealed thai the device could be used for rapid detection of EtOH conlem in various beverages such as aleoholic beverages. isotonic drinks. soft drinks and fruit juices sold in Malaysia. The sensor used was high in accuracy and reliability. where it could detect EtOH content as low as 0.1% (vlv). Wilh the lowest vollage output ofO.4JV.